Morphological ontogeny of Achipteria punctata (Acari: Oribatida: Achipteriidae) - Seniczak, Anna; Seniczak, Stanisław (Zootaxa, 2018)
The morphological ontogeny of Achipteria punctata (Nicolet, 1855) is redescribed and illustrated. The adult of this species has genu IV approximately as long as tibia IV, seta bv’’ on femur II is as long as seta d, with short seta l’ on femur III and smooth claws of all legs. The juveniles of A. punctata are stocky, with most prodorsal setae short and smooth, except for slightly longer and barbed seta ro, and gentle reticulation of cuticle between the bothridia and in the posterior part of prodorsum. In the larva, most gastronotal setae are short, thick and barbed, except for smooth c2, c3 and h2; in the nymphs the gastronotal setae are short, thin and finely barbed. In the juveniles of A. punctata, setae of l-series on legs are not thickened.